INFLUENCE OF SPERMATIC CORD BLOOD VESSELS COMPRESSION ON SPERMATOGENESIS - Глодан, О.Я. (World of Medicine and Biology, 2014)
Experimental results showed that testicular circulatory hypoxia of 15 and 30 minutes duration causes significant structural changes in if, with decrease of convolute semini ferous tubules diameter, decrease of amount of the developing spermatogenic cells in them, especially pachytene spermatocytes and stage seven spermatides, which are extra sensitive to circulatory hypoxia.
Keywords: testis; hypoxia; spermatogenesis